The impact of philosophical inquiry method on classroom engagement and reasoning skills of low achievers - Wan Yusoff, Wan Mazwati (Sciedu Press, 2018)
This research project attempted to investigate the impact of applying philosophical inquiry method of teaching on classroom engagement and reasoning skills of low achievers. Low achievers are those who have the potential to succeed but lagged behind because of several factors that demotivate them to perform at their highest ability. In this study, low achievers were students who failed or obtained the lowest grades in previous standardized school examination. They were 22 students aged 12-13 years old from a school in Gombak district, Malaysia. The students were observed and video recorded while participating in discussing the questions they had formulated in response to the given stimulus materials. Many assumed and projected that these students would not succeed in school and life; and would not have the intelligence to engage in discussion that employed higher order thinking. However, the findings revealed that when low achievers were given opportunities to voice out their opinions in dialogic pedagogy, they demonstrated the ability to be focused and engaged in classroom discussion. Furthermore, this pedagogy has proven effective in stimulating higher order thinking or reasoning skills among low achievers. Specifically, this study found indicators of behavioral, emotional and agentic engagement among low achievers; and demonstrated that low achievers were capable of asking higher order thinking questions, clarifying meanings, giving examples, making conclusion and inductive reasoning, distinguishing and classifying ideas.